Investigation on the vanadium redox flow battery energy storage system (VRB-ESS) - Tay, Xiang Jue (2014)
Vanadium Redox Flow Battery (VRB) possess high potential as an energy storage system. Charging and discharging model of VRB are developed to investigate the design features and operating performances of the Vanadium Redox Battery Energy Storage System during the charging and discharging process. Nernst equation is used to determine the stack voltage. MATLAB, Simulink is used to develop the model and perform the simulations. Stack voltage, output voltage, State of Charge (SOC) and losses are determined and monitored. The results shows that the accuracy of output voltage of the VRB are dependent on the accuracy on SOC estimation and pump current modelling and the output voltage are affected largely by the pump current and the SOC.